Pendampingan Pengelolaan Keuangan Masjid Untuk Peningkatan Akuntabilitas Sosial - Liana Dewi; Rafliana Mukhtar Renggana (LPPM Universitas Trunojoyo Madura, 2022)
Financial management is very important for various institutions that base their activities on profit or non-profit. The mosque is a non-profit religious institution. Currently the mosque is not only a place of worship but also has an important social role. The current management of the mosque is not only on the physical cleaning of the mosque but also on more complex matters, one of which is the financial management of the mosque. Although mosque financial management is important, some mosques still have not implemented financial management systematically. This community service aims to implement a financial management system for non-profit institutions. The mosque financial management training was carried out with partners from the Tasik Beberesih Masjid (TBM) community. The training participants are people who are active as TBM administrators who also act as mosque treasurers in their respective neighborhoods. The training is located at the Muhajirin Mosque which is located at Jalan Saptamarga No. 3 City of Tasikmalaya, West Java. The implementation of the service begins with collecting information regarding the financial management needs of the participants, followed by the preparation of training programs with materials that have been adapted to the needs of participants. After the training is carried out, the next stage is to review the extent to which the material provided can be implemented by the participants. Participants gain understanding and knowledge of systematic and simple recording of mosque financial management.